Commitment Factor in the Islamic Elementary School Environment - Husni Awali (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
This study aims to see how much influence leadership and motivation have on Teacher Commitment in one of the Islamic elementary schools in Bekasi City, Indonesia. This type of research is qualitative research by distributing questionnaires to teachers as many as 48 people. The results of this study indicate that: Simultaneously leadership and motivation affect teacher commitment, and partially leadership and motivation affect teacher commitment.